2015
DOI: 10.1039/c5cp02169c
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine condensation catalyzed by 1-ethyl-3-methylimidazolium acetate: mechanistic insight from NMR spectroscopy

Abstract: The basic ionic liquid 1-ethyl-3-methylimidazolium acetate ([C2C1Im][OAc]) could efficiently catalyze the conversion of 2-amino-2-deoxy-d-glucose (GlcNH2) into deoxyfructosazine (DOF) and fructosazine (FZ). Mechanistic investigation by NMR studies disclosed that [C2C1Im][OAc], exhibiting strong hydrogen bonding basicity, could coordinate with the hydroxyl and amino groups of GlcNH2via the promotion of hydrogen bonding in bifunctional activation of substrates and further catalyzing product formation, based on w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 52 publications
(122 reference statements)
2
59
0
Order By: Relevance
“…DMSO as a co‐solvent further enhanced the total yield of DOF and FZ to 49 %. The mechanism was studied in detail by NMR spectroscopy by using [Bmim]OAc as solvent/catalyst . The bifunctional effects of [Bmim]OAc indicated that the most acidic hydrogen atom on the imidazole ring might promote the intermolecular proton exchange of OH and NH 2 groups, whereas the OAc − anion, as a strong hydrogen‐bond acceptor, formed hydrogen bonds with these groups.…”
Section: Chitin Conversion Into Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…DMSO as a co‐solvent further enhanced the total yield of DOF and FZ to 49 %. The mechanism was studied in detail by NMR spectroscopy by using [Bmim]OAc as solvent/catalyst . The bifunctional effects of [Bmim]OAc indicated that the most acidic hydrogen atom on the imidazole ring might promote the intermolecular proton exchange of OH and NH 2 groups, whereas the OAc − anion, as a strong hydrogen‐bond acceptor, formed hydrogen bonds with these groups.…”
Section: Chitin Conversion Into Chemicalsmentioning
confidence: 99%
“…The mechanism was studied in detail by NMR spectroscopy by using [Bmim]OAca ss olvent/catalyst. [100] The bifunctionale ffects of [Bmim]OAc indicated that the most acidic hydrogen atom on the imidazole ring mightp romote the intermolecular proton exchange of OH and NH 2 groups, whereas the OAc À anion,a sastrongh ydrogen-bond acceptor, formed hydrogen bondsw ith these groups. In addition, the basicity of the anion also facilitated the interconversion of the a-anomera nd the banomer and thus enhanced the effective concentration of open-chain GlcNH 2 .T he catalytic performance was attributed not only to activationt hrough hydrogen-bonding interactions as am ajor driving force, but also to the activation of the lonepair electrons of the nitrogen atom on the sugar substrate acting as anucleophile.…”
Section: Heterocyclic Pyrazinesmentioning
confidence: 99%
“…To further elucidate the interaction between GlcNH 2 and SnCl 4 in ZnCl 2 molten salt hydrate medium at a molecular level, NMR titration was employed . Although high ZnCl 2 concentration could lower the sensitivity of the 1 H NMR measurements, well‐resolved signals of GlcNH 2 were observed in the 13 C spectrum.…”
Section: Chemical Shift Drifts and Signal Broadeningsmentioning
confidence: 99%
“…Our research group has previously demonstrated its power in the biorefinery by the utilization of NMR to study the degradation of lignocellulosic biomass, inulin biomass and chitin biomass. [26][27][28][29] Unfortunately, the commonly employed one dimensional (1D) NMR, especially 1 H NMR, is limited for complex mixture analysis, because of the spectral complexity, narrow spectra width and closely spaced signals, which commonly causes the signals to overlap. Therefore, extensive utilization of the 1D NMR methods in biomass conversion study is often confounded by unclear interpretation.…”
Section: Introductionmentioning
confidence: 99%